Pinvox Method to Enhance Self-Study in Blended Learning: Experiences at University of Bucharest - Canessa, Enrique; Logofatu, Bodgan (International Journal of Emerging Technologies in Learning (iJET), 2013)
We report results on the first large-scale trialimplementation of the new Pinvox algorithm carried out atthe Department of Distance Learning (DL) of the Universityof Bucharest to encourage hundreds of Bachelor and MasterDL students to perform their self-study. Pinvox is an opensource tool that helps to ensure "on-line attendanceâ? and toinduce â??student's attentionâ? through the identification ofdifferent, randomly selected, brief audio PINs embeddedautomatically in videos or audio files assigned to eachstudent. We argue that checking how students watched avideo lecture has many advantages in the formativeassessment work.